The genome of the platyfish, Xiphophorus maculatus, provides insights into evolutionary adaptation and several complex traits - Schartl, Manfred (2013)
Several attributes intuitively considered to be typical mammalian features, such as complex behavior, live birth, and malignant diseases like cancer, also appeared several times independently in so-called “lower” vertebrates. The genetic mechanisms underlying the evolution of these elaborate traits are poorly understood. The platyfish, Xiphophorus maculatus, offers a unique model to better understand the molecular biology of such traits. Herein we detail sequencing of the platyfish genome. Integrating genome assembly with extensive genetic maps uncovered that fish, in contrast to mammals, exhibit an unexpected evolutionary stability of chromosomes. Genes associated with viviparity show signatures of positive selection identifying new putative functional domains and rare cases of parallel evolution. We also discovered that genes implicated in cognition possess an unexpected high rate of duplicate gene retention after the teleost genome duplication suggesting a hypothesis for the evolution of the great behavioral complexity in fish, which exceeds that in amphibians and reptiles.